Depression and Amputation: A Narrative Literature Review - Arazy Gifta Prima (HM Publisher, 2021)
Traumatic limb amputation leads to higher levels of anxiety, depression, and emotional stress in the individual. Adaptation to this event encounters many physical changes, such as impairments in physical functioning, prosthesis use, pain, changes in employment status or occupation, and alterations in body image. This review aimed to explain depression in amputation patients. People who experience amputation, which is the loss of one or several limbs, can experience a number of psychological problems, such as posttraumatic stress disorder, depression, and anxiety. Amputation can be a traumatic experience and cause prolonged stress. This can happen due to the loss of limbs that are considered important for everyday life. Despite this, it was seen that older people had lower anxiety and depression scores than their younger counterparts. This may be because older amputees have lower expectations and demands and are less likely to have emotional upset. In conclusion, amputees have a large number of psychosocial concerns which need to be addressed to provide holistic care and a better quality of life. The affected, which were optimistic, had more social support, had a pain-free life, and had to visit hospitals less, were significantly less anxious than their counterparts.